Pharmacoepidemiological Evaluation Of Antifungal Drug Therapy Used In HospitalUniversiti Sains Malaysia (HUSM) - Mohammed, Hamid Mahmoud Nasreldeen (2010)

(untitled)
Today, managing fungal infection is one of the challenges doctors have to face worldwide. Fungal infection is considered as one of the main causes of morbidity and mortality among patients, especially those who are severely immunocompromised. In the current work, retrospective study was undertaken in order to determine the epidemiology and management of fungal infection among both outpatients and hospitalized patients at Universiti Sains Malaysia Hospital (HUSM).